Genotypes of kappa-casein gen in creole cattle of Bambamarca district (Cajamarca, Peru) - Almeyda R., Marcos (2016)
The aim of this study was to determine the allelic and genotypic frequency of kappacasein gene (κ-CN) in creole cattle. For this purpose, 48 blood samples were collected from animals in nine villages of the Bambamarca district, Cajamarca, Peru. DNA was extracted and genotyping was performed by PCR-RFLP analysis of κ-CN gene. Genotype frequencies of 0.56, 0.27 and 0.17 for the AB, AA and BB genotypes were found, while the allele frequencies were 0.552 and 0.448 for alleles A and B respectively. It was concluded that the tested group had a low proportion of individuals with the desired BB genotype that favors the production of cheese.